2017
DOI: 10.1002/msc.1187
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of revision total hip replacement: A multi‐centre survey of current practice

Abstract: This survey adds to sparse information about rehabilitation RTHR. No consensus emerged about optimal rehabilitation. The diversity in approach and lack of clear structure suggests work is needed to develop rehabilitation interventions that are tailored to this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In 2016, a national survey of care pathways for patients receiving revision surgery for prosthetic joint infection found that there was a lack of tailored physiotherapy and occupational therapy services for patients [21]. The provision of rehabilitation after revision total hip replacement was evaluated in a national survey in 2016, which found there was considerable variation in service provision and a lack of consensus regarding optimal rehabilitation strategies [15]. Our study adds to this body of evidence, nding that physiotherapy provision for patients undergoing revision TKR is variable and the same as that provided to patients undergoing primary TKR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, a national survey of care pathways for patients receiving revision surgery for prosthetic joint infection found that there was a lack of tailored physiotherapy and occupational therapy services for patients [21]. The provision of rehabilitation after revision total hip replacement was evaluated in a national survey in 2016, which found there was considerable variation in service provision and a lack of consensus regarding optimal rehabilitation strategies [15]. Our study adds to this body of evidence, nding that physiotherapy provision for patients undergoing revision TKR is variable and the same as that provided to patients undergoing primary TKR.…”
Section: Discussionmentioning
confidence: 99%
“…Contacts were then e-mailed a link to the online survey, with up to two reminders sent to non-responders. The survey, administered using Online Surveys (www.onlinesurveys.ac.uk), consisted of 27 questions which were developed by the research team, informed by previous national surveys of rehabilitation services for primary TKR [14] and revision hip replacement [15]. The survey questions explored preoperative, in-patient and post-discharge care including pre-operative education, inpatient physiotherapy and occupational therapy, rehabilitation-speci c discharge criteria, and provision of post-discharge rehabilitation.…”
Section: National Survey Of Rehabilitation Provision For Revision Tkrmentioning
confidence: 99%
“…While the benefits of physiotherapy after THA are generally acknowledged [ 1 ], and it frequently takes place in acute care clinics [ 17 , 18 ], there is a lack of consensus on the exact therapy program and only little evidence from controlled clinical trials, as a systematic review of the literature that appeared after 2008 [ 19 ] has shown. Other reviews and meta-analyses confirmed this view [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a registry‐based analysis demonstrated poorer clinical outcomes on hip pain and function for patients after revision THR than following primary THR (Stisen et al., 2022). Evidence on revision THR in terms of the effectiveness of pain relief and functional improvement is sparse (Singh & Lewallen, 2013), and no consensus exists on optimal rehabilitation after revision THR (Newman & Barker, 2017). This calls for research exploring different rehabilitation approaches to improve clinical outcomes for patients after revision THR.…”
Section: Introductionmentioning
confidence: 99%